Fighting the Sweatshop in Depression Ontario: Capital, Labour and the Industrial Standards Act - Klee, Marcus (Labour / Le Travail, 2000)
The judicial and political failure of Prime Minister R. B. Bennet's New Deal legislation during the mid-1930's shifted the struggle to reconstitute capitalism to the provincial and municipal levels of the state. Attempts to deal with the dislocations of the Great Depression in Ontario focused on the "sweatshop crisis" that came to dominate political and social discourse after 1934. Ontario's 1935 Industrial Standards Act (ISA) was designed to bring workers and employers together under the auspices of the state to establish minimum wages and work standards. The establishment of New Deal style industrial codes was premised on the mobilization of organized capital and organized labor to combat unfair competition, stop the spread of relief-subsidized labor, and halt the predations of sweatshop capitalism. Although the ISA did not bring about extensive economic regulation, it excited considerable interest in the possibility of government intervention. Workers in a diverse range of occupations, from asbestos workers to waitresses, attempted to organize around the possibility of the ISA. The importance of the ISA lies in what it reveals about the nature of welfare, wage labor, the union movement, competitive capitalism, business attitudes toward industrial regulation, and the role of the state in managing the collective affairs of capitalism. The history of the ISA also suggests that "regulatory unionism," as described by Colin Gordon in his work on the American New Deal, may have animated key developments in Canadian social, economic, and labor history.